Deconstruction of the Prevention of Knee Osteoarthritis by Swimming Based on Data Mining Technology. (16th August 2022) - Yin, Jianxia; Li, Qing; Song, Yao
Abstract : With the continuous development of big data and the continuous improvement of people's living standards, increasingly attention is paid to physical health. Swimming in this sport is effective in preventing the occurrence of arthritis. This paper analyzes the prevention and exploration of arthritis and relies on the traditional method of retrieving clinical literature on the treatment of knee osteoarthritis with traditional Chinese medicine and internal medicine, which requires a lot of manpower and material resources. At this time, the role of data mining technology is brought into play. This article analyzes the prevention of arthritis by swimming. If you rely on the traditional retrieval of clinical literature on the treatment of knee osteoarthritis with traditional Chinese medicine and internal medicine, you will find a lot of disordered data. It takes a lot of manpower and material resources to sort out the summary, and at this time, the role of data mining (DM) technology is brought into play. In this paper, the relevant information of the literature that meets the requirements is established in an Excel database, and the data of the relevant information is entered. Through sorting and analysis, the TCM syndrome types of knee osteoarthritis are summarized. Then, DM technology was used to carry out statistical analysis of frequency and prescription, to summarize the distribution characteristics of the corresponding knee osteoarthritis, TCM syndrome types, and the weight of each syndrome type, and to make a preliminary discussion at the same time. Finally, it is concluded that there are better prevention methods for arthritis in the research methods of traditional Chinese medicine. DM technology has been increasingly applied to all aspects of traditional Chinese medicine. DM technology has improved its research efficiency by 38% and achieved great results, which will play a greater role in promoting the research process of TCM syndrome.